The answer is either Dr Tanenbaum or Dr hong.<span />
A, C, D, E . all of them are true.
Answer:
a^3 - b^2 for a = 3 and b = 1/2
3^3 - (1/2)^2
= 27 - 1/4
= 26 3/4
Step-by-step explanation:
Answer:
2/9 and 7/4(or 1 3/4)
Step-by-step explanation:
A reciprocal is just the original number flipped.
Step-by-step explanation:
step 1. The perimeter (P) is the length around the triangle.
step 2. P = 6 + 5 + L (the length of the hypotenuse)
step 3. L = sqrt(6^2 + 5^2) = sqrt(61) where sqrt is the square root
step 4. P = 11 + sqrt(61) = 18.81.